Inovasi Pelayanan Kependudukan Berbasis Braille di Kota Malang - Setiawan, M N Romi A; Dewi, Dewa Ayu Putu Shandra; Helda, Maria Elfrida Nona (Yayasan Lentera Avanya Nagari, 2023)
This research aims to determine the service innovation